Perfil epidemiológico da mortalidade materna no hospital de referência nacional da Guiné-Bissau : 2013 a 2018 - Mendes, Aminata (2020)
Maternal mortality is a phenomenon that directly affects women's reproductive health and the social development of a country, reflecting the quality of health services, including the accessibility of health care provided, the referral network, as well as the quality of care. assistance provided to women. Objective: To analyze and describe the causes and epidemiological profile of maternal mortality at the National Reference Hospital in Guinea-Bissau between 2013 and 2018. Method: Retrospective descriptive cross-sectional study with a quantitative and qualitative approach through data collection in medical records and interviews with family members and puerperal women in order to understand maternal death from the perspective of the family member and delays in obstetric care. Microsoft Office Excel, Software for Statistics and Data Science-Stata.11.2 programs were used for data management and statistical analysis. An exploratory descriptive analysis was carried out involving the study variables. Result: 557 maternal deaths were identified and analyzed at the Simão Mendes National Hospital. The highest proportion of deaths is in the age group between 20 and 29 years old. Married women represent 81.6% (444) of deaths. 86.2% (480) of these women had less than 8 years of schooling. 59.6% (332) were rural residents. 82.9% (462) were housewives. 52.8% (294) were Muslims. 31.2% (174) were Fula, followed by Balanta with 22.8% (127). Prenatal care was not performed by 40.7% (227) of the deceased. It is revealed that 56% (312) of deaths occurred during the term of pregnancy.43.9% (244) deaths occurred in normal deliveries. 44.9% (250) of these deaths at delivery. The main causes of death found were hemorrhage 50.4% (281), followed by hypertension with 17.4% (97). Conclusion: Those of maternal deaths predominated in young women, with little education, without paid employment due to direct obstetric causes that could have been avoided with improved comprehensive care for pregnant women, starting from prenatal care to the availability of intervention mechanisms in opportune time.